2D molybdenum and vanadium nitrides synthesized by ammoniation of 2D transition metal carbides (MXenes). Issue 45 (14th November 2017) - Urbankowski, Patrick; Anasori, Babak; Hantanasirisakul, Kanit; Yang, Long; Zhang, Lihua; Haines, Bernard; May, Steven J.; Billinge, Simon J. L.; Gogotsi, Yury
Abstract : Synthesis of 2D transition metal nitrides can be achieved by ammoniation of carbide MXenes (Mo2 CTx and V2 CTx ) at elevated temperatures. Abstract : MXenes are a rapidly growing class of 2D transition metal carbides and nitrides, finding applications in fields ranging from energy storage to electromagnetic interference shielding and transparent conductive coatings. However, while more than 20 carbide MXenes have already been synthesized, Ti4 N3 and Ti2 N are the only nitride MXenes reported so far. Here by ammoniation of Mo2 CTx and V2 CTx MXenes at 600 °C, we report on their transformation to 2D metal nitrides. Carbon atoms in the precursor MXenes are replaced with N atoms, resulting from the decomposition of ammonia molecules. The crystal structures of the resulting Mo2 N and V2 N were determined with transmission electron microscopy and X-ray pair distribution function analysis. Our results indicate that Mo2 N retains the MXene structure and V2 C transforms to a mixed layered structure of trigonal V2 N and cubic VN. Temperature-dependent resistivity measurements of the nitrides reveal that they exhibit metallic conductivity, as opposed to semiconductor-like behavior of their parent carbides. As important, room-temperature electrical conductivity values of Mo2 N and V2 N are three and one order of magnitude larger than those of the Mo2 CTx and V2 CTx precursors, respectively. This study shows how gas treatment synthesis such as ammoniation can transform carbide MXenes into 2D nitrides with higher electrical conductivities and metallic behavior, opening a new avenue in 2D materials synthesis.